Structural and optical properties of ZnSe and ZnSe/ZnS quantum dots prepared by using green method - Belaribi, Imene; Balaban, Mesut; Bendella, Soumia; Unlu, Hilmi (SPRINGER HEIDELBERG, 2025)
We report the green synthesis, structural characterization, optical measurements, and theoretical modeling of ZnSe and ZnSe/ZnS quantum dots (QDs) synthesized via a rapid aqueous method using thioglycolic acid (TGA) as a stabilizer. The synthesis was carried out at 90 degrees C and pH 8.5, employing zinc acetate, NaHSe as a selenium source, and thiourea for ZnS shell growth. X-ray diffraction (XRD) analysis confirmed cubic-phase ZnSe with a dominant (111) peak, while ZnSe/ZnS core-shell samples exhibited additional peaks attributed to hexagonal ZnS, indicating successful passivation. Williamson-Hall analysis yields a core crystallite size of similar to 2.3 nm and reveals a compressive interfacial strain of - 2.2% in the core-shell heterostructure. Optical characterization via UV-Vis and photoluminescence (PL) spectroscopy techniques showed redshift in both absorption and emission with increasing reaction time and temperature, consistent with quantum size effects and shell-induced modifications. Theoretical modeling by using modified Brus equation based on Kane's effective mass approximation, and a recently developed thermoelastic strain theory quantitatively explained the bandgap evolution by accounting for size-dependent confinement and elastic strain at the core-shell interface. Calculated bandgap values showed strong agreement with experimental data: 3.67-3.71 eV from absorption and 3.39-3.41 eV from PL. The integration of green chemistry and strain-sensitive bandgap engineering underscores the potential of the QDs for low-toxicity optoelectronic and biosensing applications.
Keywords: Quantum dots; ZnSe/ZnS core-shell structure; Green synthesis; Interfacial strain; Quantum confinement; XRD; Optical bandgap modeling; NANOCRYSTALS; FACILE; DEPENDENCE; GAP; Materials Science; Physics